1976
DOI: 10.1093/nar/3.9.2387
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for DNA restriction site mapping

Abstract: When a DNA molecule, enzymatically labelled with 32p at one end, is partially digested with a restriction enzyme labelled tdna fragments are obtained which form an overlapping series of molecules, all with a common labelled terminus. ta restriction map can then be constructed from an analysis of the size distribution of these molecules. This technique has been used for the restriction site mapping of cloned histone DNA (h22) where as many as 35 cleavage sites may be accurately determined in a single experiment. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
288
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 999 publications
(292 citation statements)
references
References 6 publications
(2 reference statements)
4
288
0
Order By: Relevance
“…The chromosomal localization of fliC in strain PAO was refined by Smith-Birnstiel [31] partiallSpeI complete restriction mapping with enzymes EcoRI, BglII, PstI, XhoI and NdeI (Fig. 5).…”
Section: Flic Location On the Chromosomementioning
confidence: 99%
“…The chromosomal localization of fliC in strain PAO was refined by Smith-Birnstiel [31] partiallSpeI complete restriction mapping with enzymes EcoRI, BglII, PstI, XhoI and NdeI (Fig. 5).…”
Section: Flic Location On the Chromosomementioning
confidence: 99%
“…Restriction enzyme and Southern blot analysis (Meinkoth and Wahl, 1984) revealed that one of the clones, designated POC4, contains a large part of the 5'-flanking region of the PGA gene. This clone was further characterized by combining data obtained by single and double digestions and by the method of Smith and Birnstiel (1976) (Fig. 2).…”
Section: Isolation and Cloning Of The 5'-flanking Region Of The Porcimentioning
confidence: 99%
“…4). In addition, a number of preparations of RU, TRU, and EXT, as well as other cloned satellite repeat units that have been sequenced or restriction (Smith and Birnstiel, 1976); Hid digested RU was used as a reference for numbering the fragments . Fig.…”
Section: (A) Satellite Repeat Units Inserted Into the Ecori Or Psfi Smentioning
confidence: 99%